PENGARUH PROFITABILITAS, LIKUIDITAS TERHADAP FINANCIAL DISTRESS PERUSAHAAN TEKSTIL DAN GARMEN - Nur Siti Angela Pakpahan (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study aims to analyze the effect of profitability and liquidity on financial distress in textile and garment sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. Profitability is measured using Return on Assets (ROA), while liquidity is measured using the Current Ratio (CR). Financial distress is measured using the Altman Z-Score model. This research employs a quantitative approach with secondary data obtained from the companies’ annual financial statements. The sample was determined using a purposive sampling technique, resulting in a number of companies that met the predetermined criteria. The results of the study show that, partially, both profitability and liquidity have a significant effect on financial distress. Furthermore, simultaneously, these two variables also have a significant influence on financial distress. These findings highlight that a company’s ability to generate profits and maintain liquidity